Prolonged Myocardial Regenerative Capacity in Neonatal Opossum. Issue 2 (26th May 2022) - Nishiyama, Chihiro; Saito, Yuichi; Sakaguchi, Akane; Kaneko, Mari; Kiyonari, Hiroshi; Xu, Yuqing; Arima, Yuichiro; Uosaki, Hideki; Kimura, Wataru
Abstract : Background: Early neonates of both large and small mammals are able to regenerate the myocardium through cardiomyocyte proliferation for only a short period after birth. This myocardial regenerative capacity declines in parallel with withdrawal of cardiomyocytes from the cell cycle in the first few postnatal days. No mammalian species examined to date has been found capable of a meaningful regenerative response to myocardial injury later than 1 week after birth. Methods: We examined cardiomyocyte proliferation in neonates of the marsupial opossum ( Monodelphis domestica ) by immunostaining at various times after birth. The regenerative capacity of the postnatal opossum myocardium was assessed after either apex resection or induction of myocardial infarction at postnatal day 14 or 29, whereas that of the postnatal mouse myocardium was assessed after myocardial infarction at postnatal day 7. Bioinformatics data analysis, immunofluorescence staining, and pharmacological and genetic intervention were applied to determine the role of AMPK (5′-AMP–activated protein kinase) signaling in regulation of the mammalian cardiomyocyte cell cycle. Results: Opossum neonates were found to manifest cardiomyocyte proliferation for at least 2 weeks after birth at a frequency similar to that apparent in early neonatal mice. Moreover, the opossum heart at postnatal day 14 showed substantial regenerative capacity both after apex resection and after myocardial infarction injury, whereas this capacity had diminished by postnatal day 29. Transcriptomic and immunofluorescence analyses indicated that AMPK signaling is activated in postnatal cardiomyocytes of both opossum and mouse. Pharmacological or genetic inhibition of AMPK signaling was sufficient to extend the postnatal window of cardiomyocyte proliferation in both mouse and opossum neonates as well as of cardiac regeneration in neonatal mice. Conclusions: The marsupial opossum maintains cardiomyocyte proliferation and a capacity for myocardial regeneration for at least 2 weeks after birth. As far as we are aware, this is the longest postnatal duration of such a capacity among mammals examined to date. AMPK signaling was implicated as an evolutionarily conserved regulator of mammalian postnatal cardiomyocyte proliferation.